Association between shift work, salivary cortisol levels, stress and fatigue in nurses: integrative review - Dnieber Chagas de Assis; Deisy Vivian de Resende; Maria Helena Palucci Marziale (Universidade Federal do Rio de Janeiro, 2018)
ABSTRACT Objective: This study aimed to identify scientific evidence about the association between shift work and changes on the cortisol circadian rhythm, stress and fatigue in nurses. Method: We found 1046 articles published between 2006 and 2016 in the Medline, LILACS, WOS, Scopus and SciElo databases, three articles were included in this review. Results: The studies presented low methodological rigor and inconclusive results due to methodological diversity and small sample size. Thus, based on the existing literature, it was not possible to determine the existence of a significant association between shift work, cortisol levels, stress and fatigue in nurses. Conclusion: The strategies required to obtain reliable and comparable results include the adoption of standard methods of participant selection, sample collection and analysis, and use of validated psychometric instruments.